2013
DOI: 10.1080/1046669x.2013.805616
|View full text |Cite
|
Sign up to set email alerts
|

Critical Social Theory and the Emancipation of Marketing Channels Knowledge

Abstract: Over 25 years ago, Bartels (1988) deftly chronicled the history of marketing thought, reifying the inextricable linkage between distributive sciences, utility creation, and marketing practices. The earliest writings in marketing charted the physical movement of goods through the distribution system. There existed misconceptions of channel members, compelling justification of their role sets in creating efficiencies and utilities that delivered value to customers. Bartels (1988) noted that attributions of inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…For example, if the manufacturer possesses a good social bond with the retailer, this may result in the retailer's Downloaded by [New York University] at 01:54 07 July 2015 positive social outcomes and the perception of a fulfilling interaction. Researchers have also addressed satisfaction in its social aspect and described it as the evaluation of interaction experiences (Scheer & Stern, 1992) and a reflection on the psychosocial well-being of the firm (Gassenheimer & Ramsey, 1994;Pelton, 2013).…”
Section: Retailers' Economic and Social Satisfactionmentioning
confidence: 99%
“…For example, if the manufacturer possesses a good social bond with the retailer, this may result in the retailer's Downloaded by [New York University] at 01:54 07 July 2015 positive social outcomes and the perception of a fulfilling interaction. Researchers have also addressed satisfaction in its social aspect and described it as the evaluation of interaction experiences (Scheer & Stern, 1992) and a reflection on the psychosocial well-being of the firm (Gassenheimer & Ramsey, 1994;Pelton, 2013).…”
Section: Retailers' Economic and Social Satisfactionmentioning
confidence: 99%
“…Within philosophy, sociology, and educational research, critical theory has been widely used to debate, for instance, the relations of injustice and domination (Forst, 2001;Bernstein, 2005), the fundamental transformations in the world economy, politics, and culture (Kellner, 2002), and adult learning and education (Mezirow, 1981). With regard to research within organisations, critical theory has been found to be useful in generating new understanding of micro-politics in organisational work (Toegel, Kilduff & Anan, 2013), analysing organisational science (Steffy & Grimes, 1986), and broadening marketing channels for education, research and practice (Pelton, 2013). Critical theory has, moreover, been applied to extend entrepreneurship theory with the aim of encompassing social change.…”
Section: Critical Theory and Its Historymentioning
confidence: 99%
“…Social marketing is becoming a popular method to attract customers to networks. Social marketing is an essential component of marketing planning, it helps get more exposure to interested customers through network, and online review sites become important sources of information in tourism product purchases (Pelton, 2013). Spark et al (2013) examined experimentally how source, content style, and peripheral credibility cues in online postings affect four consumer beliefs, and how those in turn affect behaviors and purchase intentions for an eco-resort.…”
Section: Introductionmentioning
confidence: 99%